Integration of MQTT and Augmented Reality using Dobot Magician Lite Robot - Rante, Hestiasari; Hanifati, Kirana; Arief, Muhammad Fauzan; Sukaridhoto, Sritrusta; Zainuddin, M. Agus; Mezouar, Youcef; Hill, David R. C. (JOIV : International Journal on Informatics Visualization, 2025)
As robotics education evolves, there is a growing demand for effective tools that offer hands-on learning experiences while addressing the traditional challenges such as limited interactivity, high costs, and the need for sophisticated technical knowledge. This paper explores the integration of wireless controllers and Augmented Reality (AR) image tracking with the Dobot Magician Lite robotic platform to enhance robotics learning. The proposed solution utilizes MQTT (Message Queuing Telemetry Transport), a lightweight messaging protocol, to enable intuitive and user-friendly wireless control of the robot. By using AR image tracking, students may see and operate virtual overlays that are aligned with the actual robot, bridging the gap between theoretical understanding and practical application. This technique not only streamlines the control procedure, but it also creates an interesting and immersive learning environment, making robotics education more accessible to a larger range of people. Team Alpha (n=4) and Team Beta (n=4) conducted testing in Indonesia and found promising results: average response time was 160 ms and 165 ms, respectively; movement accuracy was 1.5 mm and 1.7 mm; AR display quality received scores of 8.8 and 8.6; and user satisfaction ratings were 9.0 and 8.9. Both teams reported great system adaptability and minimal issue frequency, with Team Beta mentioning minor performance difficulties including occasional latency.  These findings highlight the effectiveness and reliability of the proposed system, supporting its potential for broader application in robotics education.